Educação brasileira e identidade negra em Kabengele Munanga - SILVA, Cristiano Pinto da (2009)
This study aimed to identify the theoretical support that grounds the production of Kabengele Munanga and characterize the conception of black identity in the production of the author, and its contributions to the curriculum of the Brazilian Education. To achieve these objectives were researched two books of the author that deal specifically about the construction of the black identity. We also researched the bibliographic production realized by Brazilian and foreigner researchers that deal about the racial relations, the construction of the black identity and its implications for the Brazilian educational context, that are related to the academic production of Kabengele Munanga. This work was based on a theoretical research, starting from the reading of the documents and bibliography about the construction of the black identity and education. The school is understood as a social institution that generates values and reproduces the culture, therefore, becomes of fundamental importance the action of the school in avoiding any discrimination, being it for race, ethnicity, social rate, gender, religion or age. The trajectory of discrimination, segregation and denial of the black identity in all socialization institutions, including the school awakens the debate about initiatives for the statement of the rights of access to the education in all levels, understanding the great importance of the education in changing an unfavorable social context to the black people, as the Brazilian is. The denial of the black identity is characterized as a historical fact since the colonization of Brazil, and has been frequently stated in curricular omissions that are materialized in the silence about this object of study and the African culture. In this context, the educators havent received a specific formation to handle with the ethnic cultural diversity, neither with racial matters involved in their school quotidian.